Qurban as Cultural Transformation and Islamic Moderation in Indonesia: from Religious Ritual to Humanitarian Ethics and Interfaith Coexistence - Mohammad Muslih; Ide Mafaza Sansayto; Ahmad Inzimam Haq (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Agung, Dewa Agung Gede, Ahmad Munjin Nasih, and Bayu Kurniawan. “Local Wisdom as a Model of Interfaith Communication in Creating Religious Harmony in Indonesia.” Social Sciences & Humanities Open 9 (2024): 100827. Ahmad, Abdulloh Sajjad. “Religious Moderation in Islamic Rreligious Practices Through Wasathiyah Concept.” Sunan Kalijaga International Journal on Islamic Educational Research 5, no. 2 (2021): 72–84. Al-Attas, S. “Islam and Secularism (Kuala Lumpur, International Institute of Islamic Thought and Civilization).” International Islamic University Malaysia, 1993. Al–Attas, Syed Muhammad Naquib. Prolegomena to the Metaphysics of Islam. Penerbit UTM Press, 2014. Ali, A. Mukti. An Introduction to Religious Research Methodology. Disunting oleh Abdullah Taufik dan Karim Rusli. Yogyakarta: Tiara Wacana Yogya, 1990. Arkoun, Mohammed, and Robert D Lee. Rethinking Islam: Common Questions, Uncommon Answers. Routledge, 2019. Asad, Talal. Genealogies of Religion: Discipline and Reasons of Power in Christianity and Islam. Jhu Press, 1993. Basyir, Damanhuri. “The Practice of Qurban: Integrating Economic, Social, and Environmental Dimensions.” El-Sunan: Journal of Hadith and Religious Studies 2, no. 2 (2024): 156–65. Batson, Charles Daniel. Altruism in Humans. Oxford University Press, 2011. Beatty, Andrew. “Varieties of Javanese Religion.” An Anthropological Account, 1999. Bennabi, Malik. The Question of Ideas in the Muslim World. Islamic Book Trust Kuala Lumpur, 2003. Creswell, John W. “Research Design: Qualitative, Quantitative, and Mixed Methods Approaches 4rd.” Sage publications, 2014. Creswell, John W, and Cheryl N Poth. Qualitative Inquiry and Research Design: Choosing among Five Approaches. Sage publications, 2016. Esposito, John L. What Everyone Needs to Know about Islam. Oxford University Press, 2011. Faizul, Naqibah Muhammad. “Islamic Philanthropy and the Qur’anic Approach to Scarcity: Wealth Redistribution as a Solution.” Journal of Islamic Economics and Philanthropy 7, no. 4 (2025): 223–37. Fauzi, Ahmad, dan Nur Aini. “Ibadah Kurban dalam Perspektif Fikih Sosial.” Mawaizh 4, no. 2 (2021). https://doi.org/10.32923/maw.v12i1.1752 Geertz, Clifford. “Cultures.” New York: Basic Books, Inc, 1973. Gil-Gimeno, Javier, and Celso Sanchez Capdequi. “The Persistence of Sacrifice as Self-Sacrifice and Its Contemporary Embodiment in the 9/11 Rescuers and COVID-19 Healthcare Professionals.” Religions 12, no. 5 (2021): 323. Hefner, Robert W. Civil Islam: Muslims and Dmocratization in Indonesia. Princeton University Press, 2011. Huda, Mohamad Miftahul, Choirul Mahfud, dan Ahmad Wibowo. “Islamic Interdisciplinary Studies and Its Contribution to the Development of Islamic Higher Education in Indonesia.” Journal of Social Studies Education Research (2021): 47–52. https://doi.org/10.17499/jsser.25240 Howell, Julia Day. “Sufism and the Indonesian Islamic Revival.” The Journal of Asian Studies 60, no. 3 (2001): 701–29. Jameelah, Mariyam, and Rahmat Aiman. “Universal Values as a Meeting Point in Abrahamic Religions: Insights from Schuon and Smith.” Peradaban Journal of Religion and Society 4, no. 1 (2025): 29–46. Kamali, Hashim. “Principles of Islamic Jurisprudence, Cambridge, Islamic Texts Society.” Karmali, Ayla, 2007, 3–4. Kamali, Mohammad Hashim. The Dignity of Man: An Islamic Perspective. Islamic Texts Society, 2002. Kathir, Ibn. “Imad Al-Din Abu Al-Fida.” Isma ‘Il, Tafsir Al-Qur’an Al-‘Azim, 1998. Murata, Sachiko, and William C Chittick. The Vision of Islam. Vol. 134. Paragon House New York, 1994. Nasr, Seyyed Hossein. “Ideals and Realities of Islam.” Religious Studies 13, no. 3 (1977). ———. “Islam and the Plight of Modern Man.” (No Title), 1975. ———. “Man and Nature: The Spiritual Crisis of Modern Man,” 1968. ———. The Heart of Islam: Enduring Values for Humanity. Zondervan, 2009. Nielsen, J S. “Akbar S. Ahmed, Islam Today: A Short Introduction to the Muslim World.” ETHNIC AND RACIAL STUDIES 22 (1999): 903. Noviandri, Raka, Elsita Insani, Latifha Umi Barakah, Sabila Ramadhani Lubis, and Wismanto Wismanto. “Qurban Sebagai Sarana Penguatan Nilai-Nilai Kebersamaan Dalam Masyarakat.” Akhlak: Jurnal Pendidikan Agama Islam Dan Filsafat 2, no. 1 (2025): 98–109. Rahman, Fazlur. Islam & Modernity: Transformation of an Intellectual Tradition. Vol. 15. University of Chicago Press, 2024. ———. Major Themes of the Qur’an. University of Chicago Press, 2009. Ramadan, Tariq. Radical Reform: Islamic Ethics and Liberation. Oxford University Press, 2009. Sarkawi, Sarkawi. “Nilai-Nilai Dakwah Dalam Ibadah Kurban.” Islamika: Jurnal Ilmu-Ilmu Keislaman 22, no. 01 (2022): 1–15. Saroglou, Vassilis. “Religion and the Five Factors of Personality: A Meta-Analytic Review.” Personality and Individual Differences 32, no. 1 (2002): 15–25. Shahsavarani, A M, E A M Abadi, and M H Kalkhoran. “Stress Assessment and Development of a Primary Care of Psychology Service.” International Journal of Medical Reviews 2, no. 2 (2015): 230–41. Smith, Wilfred Cantwell. Faith and Belief. Princeton University Press, 1979. Tenri Awaru, A Octamaya, Rudi Salam, Supriadi Torro, and Firdaus W Suhaeb. “The Islamization of the Social Sciences: A Review.” GNOSI: An Interdisciplinary Journal of Human Theory and Praxis 4, no. 3 (2021): 24–41. Voll, John O. “Fazlur Rahman. Islam and Modernity: Transformation of an Intellectual Tradition. Chicago: University of Chicago Press, 1982. 172 Pages, Index. 15.00.” Review of Middle East Studies 17, no. 2 (1983): 192–93. Woodward, Mark. “Islam in Java: Normative Piety and Mysticism in the Sultanate of Yogyakarta.” In Islam in Java: Normative Piety and Mysticism in the Sultanate of Yogyakarta. University of Arizona Press, Tucson; Association for Asian Studies Monograph, 45, 1989. Zikri, Khairullah. “Deconstructing Animal Sacrifice (Qurban) in Idul Adha.” ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin 12, no. 2 (2011): 235–54.